2020
DOI: 10.3390/agronomy10101609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fruit and Vegetable Wastes and Biodegradable Municipal Wastes Co-Mixed Composts on Nitrogen Dynamics in an Oxisol

Abstract: Organic waste generation in developing countries is increasing and appropriate disposal methods are needed. An open aerobic composting using 20 L bins was carried out using 6 composts made using ratios of 3:1, 1:2 and 1:4 fruit and vegetable wastes (FVW):biodegradable municipal waste (BMW), with and without addition of homemade indigenous microorganisms (IMO), for 30 days to monitor compost quality. The nitrogen contents of the composts ranged from 1.52 to 2.76% N equivalent to 76–138 kg N ha−1 at 5 t ha−1 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In addition, however, the decrease in the N corresponded to the increase in the NH + 4 -N and NO − 3 −N content (Figure 3), which agrees with Neina [48] who reported that N can be converted to NH + 4 and NO − 3 during mineralization. A concurrent decrease in WRW pH with an increase in NH + 4 -N and NO − 3 −N observed in this study agrees with Musa et al [49], where they reported a negative relationship between nitrate production and the pH of the soil. In this study, the higher the W:R ratio, the greater the pH, and the longer the fermentation, the lower the pH.…”
Section: Chemical Characteristics Of Wrwsupporting
confidence: 93%
“…In addition, however, the decrease in the N corresponded to the increase in the NH + 4 -N and NO − 3 −N content (Figure 3), which agrees with Neina [48] who reported that N can be converted to NH + 4 and NO − 3 during mineralization. A concurrent decrease in WRW pH with an increase in NH + 4 -N and NO − 3 −N observed in this study agrees with Musa et al [49], where they reported a negative relationship between nitrate production and the pH of the soil. In this study, the higher the W:R ratio, the greater the pH, and the longer the fermentation, the lower the pH.…”
Section: Chemical Characteristics Of Wrwsupporting
confidence: 93%
“…Better conditions for microorganisms and microbial activity are positive beyond the productive function of soil as they will increase biodiversity and influence the biogeochemical cycles that are dependent on organic matter decomposition [46,48]. Heavy metals from composts can inhibit dehydrogenase enzyme activity [6]; however, the compost heavy metals from the present composts used have been reported to be low beyond detection limits [27]. Dehydrogenase activity was reported to be higher at lower compost application rate of 20 Mg ha −1 than 80 Mg ha −1 , and it was attributed to the toxic effect of heavy metals at the higher compost application rate and the heavy metal content of the composts used [49].…”
Section: Dehydrogenase Enzyme Assaymentioning
confidence: 96%
“…It can be observed from the above results that compost functional group development can be attributed to the substrates used in making it. Composts 3:1, irrespective of IMO addition, had more pronounced functional groups located on 3347 cm −1 , 3274 cm −1 (3:1 −IMO) and 3344 and 3281cm −1 (3:1 +IMO) probably due to the ratio of fruit and vegetable wastes in the compost formulation [27] while in addition, compost 3:1 +IMO had an additional functional group located at 2932 cm −1 , possibly obtained because of the ratio of FVW used in the composting and the additional microorganism source due to the addition of indigenous microorganisms (IMO).…”
Section: Composts' Gaussian-lorenzian Fitted Curvesmentioning
confidence: 99%
See 2 more Smart Citations